2017
DOI: 10.25258/ijpcr.v9i5.8601
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Preliminary Phytochemical Screening and Free Radical Scavenging Ability of Drosera indica L.

Abstract: Aim: The present study is carried out to explore the preliminary phytochemical screening and free radical scavenging activity of the whole plant Drosera indica L. Methods: a) Phytochemical screening – The qualitative analysis of secondary metabolites is carried out by the standard qualitative methods. b) In vitro free radical scavenging activity of the ethanolic and aqueous extract of the whole plant Drosera indica L is used for the analysis .Various concentrations (100 – 500mcg/ml) of the ethanol and aqueous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…And, our study also showed that extract of R. indica revealed the presence of alkaloids, flavonoids, carbohydrates, phenol, steroids, terpenoids and tannins. The result was almost similar to the previous result (16).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…And, our study also showed that extract of R. indica revealed the presence of alkaloids, flavonoids, carbohydrates, phenol, steroids, terpenoids and tannins. The result was almost similar to the previous result (16).…”
Section: Discussionsupporting
confidence: 91%
“…Reinwardtia indica known as Pyoli in Nepali is a small evergreen shrub growing to about 1 m tall. It is widely distributed from east India, Nepal, and China at an altitude of 450 m above sea level (16). Traditionally, juice of root has been used for the treatment of fever scabies, wound, and indigestion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various sensory parameters of the plant material (such as colour, odour, size, shape, and taste) were studied by organoleptic evaluation [27].…”
Section: Organoleptic Evaluationmentioning
confidence: 99%
“…It is used in traditional Chinese medicine formulation for the treatment of acute or chronic gastritis (Cn, 2014a;2014b). Reinwardtia trigyna is used as natural herbicide and weedicide as it showed a good phytotoxic activity (Khan et al, 1998;Perveen, Qaiser, 2008;Abha, Swati, Shukla, 2013). The reported pharmacological activity of the other plants belong to the same family (flax family) are used as antioxidant, wound healing, anti-microbial, anti-inflammatory, and anti-nociceptive agent.…”
Section: Introductionmentioning
confidence: 99%